Isokinetic profile of the shoulder internal and external rotators in surfers - Madeira, Miguel (2019)
Poster presented at the 3rd International Congress of CiiEM - Research and Innovation in Human and Health Sciences. June 20-22, 2018, Campus Egas Moniz, Monte de Caparica, Portugal